Comparison of Laryngeal Mask Airway and Endotracheal Tube on Intraocular Pressure in Vitrectomy - Villyastuti, Yulia Wahyu; Wicaksono, Indrawan (JAI (Jurnal Anestesiologi Indonesia), 2024)
Background: Increased intraocular pressure (IOP) is a common complication after vitrectomy. Tracheal intubation and insertion of a laryngeal mask airway (LMA) are noxious stimuli that can increase IOP.Objective: To analyze the difference between the use of LMA and an endotracheal tube (ETT) on the increase in IOP in vitrectomy.Method: Experimental study with a randomized controlled trial design in 28 patients undergoing vitrectomy who met the inclusion and exclusion criteria. Subjects were divided into 2 groups with the use of LMA and ETT. Intraocular pressure (IOP) was measured using a Schiotz tonometer before induction of anesthesia, 5 minutes after intubation, 5 minutes before extubation, 5 minutes after extubation and 24 hours after vitrectomy in healthy eyes. The analysis was carried out with the unpaired T-test and the alternative Mann Whitney test, the results were significant if the p value <0.05.Results: The mean IOP in the LMA group was 11.71 ± 1.90 mHg before induction of anesthesia; 11.04 ± 1.71 mmHg 5 min after induction; 10.86 ± 1.44 mmHg 5 min before discharge; 12.11 ± 1,49 mmHg after removal and 12.21 ± 2.63 mmHg 24 hours after discharge. The mean IOP in the ETT group was 11.05 ± 2.57 mHg before induction of anesthesia; 14.26 ± 2.59 mmHg 5 min after induction; 11.71 ± 1.90 mmHg 5 min before extubation; 14.70 ± 0,98 mmHg after extubation and 12.74 ± 1.82 mmHg 24 hours after extubation. A significant difference in IOP was found after ETT intubation and extubation (p < 0.05).Conclusion: Endotracheal tube (ETT) significantly increases IOP compared to LMA during intubation and extubation in vitrectomy surgery.